An Estimate of the primary mass of cosmic rays at 1018 eV as inferred from Volcano Ranch data - Dova, María Teresa (2003)
Accurate measurements of the lateral distribution of extensive air showers produced by cosmic rays of energy greater than 1017 eV were made in the 1970s by Linsley. At the time, the state of knowledge about the best hadronic interaction model to use to describe such data prevented conclusions about the cosmic ray mass from being drawn. We have used a modern model, QGSJET98, to infer the primary mass from these data, using the very careful records left by Linsley. We find that at a median energy of 1018 eV, the data are well described by an iron-dominated composition (88 ± 6(stat) ± 18 (syst))%. We discuss the systematic errors in this estimate that arise from model uncertainties and from the range of energies used in the work of Linsley. These data are used with the permission of the late John Linsley to whom this work is dedicated